Upaya Meningkatkan Kemampuan Membaca Permulaan Melalui Media Flip Chart pada Anak Kelompok A di TK Islam Insan Fathonah Wonorejo Karanganyar Tahun Ajaran 2014-2015 - Sinta, Gandi; , Drs. Hasto Daryanto, M.Pd; , Willi Astuti, S.Pd., M.Hum (2015)
Reading is a good way to promote a lifelong learning. Based on Doman, best time for studying reading is together with the time when the child learn to speak, and the sensitivity of learning occurs in the age of 3 to 5. The use of simple media at children is the cause of the low reading readiness. The flip chart media is an alternative media to increase the ability of reading readiness at children on the earlier age. The purpose of this research is to increase reading readiness through flip chart media toward A group children in Islam Insan Fathonah kindergarten school. This kind of research paper is classroom action research with two cycle, work procedures, consist four steps. The subjects are teacher and children in group A in Islam Insan Fathonah kindergarten, Wonorejo, Karanganyar. The result shows that the flip chart media is able to increase reading readiness. The percentage from pre action class room research to cycle II is, pre cycle 46,35%, cycle I 55,31% and cycle III 76,14%. The conclusion of this research is that flip char media is able to raise reading readiness in kindergarten Islam Insan Fathonah in the academic year of 2014 - 2015.